Assessing neuroplasticity using magnetoencephalography (MEG) in patient with left-temporo-parietal pilocytic astrocytomas treated with endoscopic surgery - Hanani Abdul Manan,; Zamzuri Idris,; Jafri Malin Abdullah,; Mohammed Faruque Reza,; Hazim Omar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Neuroplasticity has been subjected to a great deal of research in the last century. Recently, significant emphasis has been placed on the global effect of localized plastic changes throughout the central nervous system, and on how these changes integrate in a pathological context. The present study aimed to demonstrate the functional cortical reorganization before and after surgery using magnetoencephalography (MEG) in a participant with brain tumor. Results of Visual Evoked Magnetic Field (VEF) based on functional MEG study revealed significantly different of MEG N100 waveforms before and after surgery. Larger and additional new locations for visual activation areas after the surgery were found suggesting neuroplasticity. The present study highlight a physiological plasticity in a teenage brain and the alterations regarding neural plasticity and network remodeling described in pathological contexts in higher-order visual association areas.